Viral, mycoplasma and bacterial infections in nurses with symptoms of respiratory diseases - Löwenberg, A; Orie, N G (Scandinavian journal of respiratory diseases, 1976)
A consecutive series of 282 nurses of the University Hospital, Groningen, with complaints of the nose and/or throat associated with coughing and/or hoarseness were examined between April 1965 and February 1968. The intent was to obtain information on the incidence of viral, mycoplasma and bacterial infections, and on the relationship of these infections in nurses with chronic nonspecific lung disease (CNSLD). The following results were obtained: 1. Virus infections caused by influenza virus (A, B, and C), rhinovirus, parainfluenza virus, adenovirus, respiratory syncytial virus and/or Mycoplasma pneumoniae were confirmed in 30% of the nurses examined; if influenza was excluded, this figure was 20%. 2. Rhinovirus infections were found more often than all the other virus infections together (if influenza was excluded). 3. Approximately 25% of the nurses had signs of CNSLD. 4. In the course of the virus infections, nine out of 14 nurses with a history of chronic obstructive lung disease showed symptoms of exacerbation or recurrence of a generalized bronchial obstruction. 5. There was no difference in the incidence of virus infections in the group of nurses with and without CNSLD. 6. There were more bacterial infections (without a confirmed virus infection) in the subjects with CNSLD than in those without CNSLD. 7. There were more combined viral/bacterial infections in the patients with CNSLD than in those without CNSLD. 8. Patients with influenza did not have more bacterial infections than patients with other virus infections. This is also true for patients with CNSLD and influenza when regarded separately. The patients without CNSLD tended to have more bacterial infections with influenza than with other viral infections, but the difference was not statistically significant.